EMBODIMENT OF PSYCHOLOGICAL FEATURES OF INVESTIGATORY WORKERS INTO THEIR LEGAL CONSCIOUSNESS - Chuhraeva, Anna (PSYCHOLOGICAL JOURNAL, 2019)
Introduction. The article determines the basic psychological features of police workers from all police subdivisions and, especially, distinguishes the examined aspects characteristic for investigatory workers. The conducted empiric research shows that investigatory work is related to high legal responsibility and consciousness and to a high risk, at the same time. Purpose. The research aim is to determine basic psychological features of police officers from investigatory departments that support their high legal consciousness in spite of frequent risky situations. Methods. Psycho-physiological diagnostic of police workers, especially investigatory workers, was performed with the special MBDO methods, as well as their interviewing and supervision was used. Originality of the proposed research is in the fact that professional consciousness and risk have been examined not only from the scientific position, but also in connection with the psychological features of police officers revealed with the psycho-physiological diagnostic. Conclusion. Defence of interests of the state and its citizens, which is the main task of police officers and investigating workers, especially, is related to high legal consciousness and responsibility. Such traits are formed, first of all, on the basic psychological features of police officers. The performed psycho-physiological diagnostic of police officers from special subdivisions and investigating workers has revealed their general characteristics, such as: aspiring to leadership, rivalry, dominance, overcoming of obstacles, independence in decision making and actions, deep diving into investigative tasks, aspiring is independence, independents behaviour, and spontaneity. Achievement motivation is supported by strong desire for task fulfilment and propensity to risk. Their statements and actions cannot go ahead systematic and carefully planning. We should note that the police workers from the special operative (investigatory) subdivisions manifest often such personal trait as propensity to risks. The police workers of these subdivisions are characterised by: propensity to the risk, capacity and inclination for high performance, sociability, initiative. They want to be at the centre of attention and to be as knowledgeable as possible. They are characterised by psychological hardiness and good organizational abilities. Their leadership is usually perceived by others as natural. Operative official tasks applied on the workers of investigatory subdivisions require the specific professional qualities, and adequate self-estimation is the most important one. They also should have the social-professional qualities that allow them to execute successfully difficult tasks and co-operate with other people.